Pengaruh Model Pembelajaran Discovery Learning Terhadap Hasil Belajar Siswa Kelas X.7 Pada Mata Pelajaran PPKn Di UPT SMA Negeri 3 Maros - Nur Elmi; Mutiara Bakri; Muhajir Muhajir (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research aims to determine the influence of the Discovery Learning Learning Model on the Learning Outcomes of Class X.7 Students in Civics Subjects at UPT SMA Negeri 3 Maros. The research subjects were 36 students of class X.7 UPT SMA Negeri 3 Maros for the 2023/2024 academic year. This type of research is classroom action research, the steps of action planning, action implementation, observation-evaluation, and reflective analysis are recycled. Observation, testing, and documentation are used as data collection strategies. The study findings were examined qualitatively, the results of observations showed that there was an increase from cycle I to cycle II. This is proven in the analysis of the results of student discussion/question and answer, namely in cycle I the percentage of student understanding was 100% with an average score of 82. Meanwhile in cycle II it increased with the presentation of student understanding reaching 100% with an average score of 87. The results of these calculations can be It was concluded that there was a significant influence on the discovery learning model on the learning outcomes of Class X.7 students in Civics subjects at UPT SMA Negeri 3 Maros.